Degradation of altered mitochondria by autophagy is impaired in Lafora disease. (23rd April 2018) - Lahuerta, Marcos; Aguado, Carmen; Sánchez‐Martín, Pablo; Sanz, Pascual; Knecht, Erwin
Abstract : Lafora disease (LD) is a fatal neurodegenerative disorder caused mostly by mutations in either of two genes encoding laforin and malin. LD is characterized by accumulation of a poorly branched form of glycogen in the cytoplasm of neurons and other cells. We previously reported dysfunctional mitochondria in different LD models. Now, using mitochondrial uncouplers and respiratory chain inhibitors, we have investigated with human fibroblasts a possible alteration in the selective degradation of damaged mitochondria (mitophagy) in LD. By flow cytometry of MitoTracker‐labelled cells and measuring the levels of various mitochondrial proteins by western blot, we found in LD fibroblasts a partial impairment in the increased mitochondrial degradation produced by these treatments. In addition, colocalization of mitochondrial and lysosomal markers decreased in LD fibroblasts. All these results are consistent with a partial impairment in the induced autophagic degradation of dysfunctional mitochondria in LD fibroblasts. However, canonical recruitment of Parkin to mitochondria under these conditions remained unaffected in LD fibroblasts, and also in SH‐SY5Y cells after malin and laforin overexpression. Neither mitochondrial localization nor protein levels of Bcl‐2‐like protein 13, another component of the mitophagic machinery that operates under these conditions, were affected in LD fibroblasts. In contrast, although these treatments raised autophagy in both control and LD fibroblasts, this enhanced autophagy was clearly lower in the latter cells. Therefore, the autophagic degradation of altered mitochondria is impaired in LD, which is due to a partial defect in the autophagic response and not in the canonical mitophagy signalling pathways. Abstract : The degradation of altered mitochondria (mitophagy) after treatment with uncouplers or inhibitors of the mitochondrial respiratory chain is partially impaired in fibroblasts derived from Lafora disease patients. This impairment is not due to a defect in the canonical Parkin‐dependent mitophagy signalling pathway but to a diminished formation of the autophagosomes that degrade those mitochondria.